Visceral aneurysms: Old paradigms, new insights?. Issue 1 (February 2017) - van Rijn, M.J.E.; ten Raa, S.; Hendriks, J.M.; Verhagen, H.J.M.
Abstract: True visceral artery aneurysms (VAAs) are a rare entity with an incidence of 0.01–2%. The risk of rupture varies amongst the different types of VAAs and is higher for pseudo aneurysms compared with true aneurysms. Size, growth, symptoms, underlying disease, pregnancy and liver transplantation have all been associated with increased risk of rupture. Mortality rates after rupture are around 25%. The splenic artery is most commonly affected and the etiology is predominantly atherosclerosis. Open repair can be done by simple ligation or reconstruction of the artery, while endovascular options include embolization or using a stent graft. Location, collateral circulation and medical condition of the patient should all be taken into account when an intervention is planned. We compared types of treatment and searched for risk factors for rupture but unfortunately, the level of evidence found in the literature is low. Therefore, deciding when and how to treat a patient with a VAA based on the current literature, remains challenging for clinicians.